Uji Daya Hambat Sari Daun Alpukat (Persea americana mill) terhadap Pertumubuhan Escherichia coli - Yuniarty, Tuty; Hasjim, Lisfaresliana (Poltekkes Kemenkes Kendari, 2017)
Avocado leaves (Percea americana mill) are a part of avocado plants that have benefits as traditional medicines. Avocado leaves are potentially used as anti-diarrhea based on the content of chemicals contained therein, namely saponins, alkaloids, tannins, flavanoids, polyphenols, quercetin which are used to kill pathogenic bacteria, one of which is Escherichia coli. Escherichia coli is an opportunist germ that is commonly found in the human intestine as a normal flora. The purpose of this study was to determine the inhibition of avocado leaf extract on the growth of Escherichia coli bacteria. This type of research is an Experimental laboratory. The research design used in this study was static group comparison because this study was conducted to see differences in concentrations of 10%, 15%, 25%, 50% and 75% of avocado leaf extract in inhibiting the growth of Escherichia coli bacteria by looking at the clear zone formed. The results showed that at a concentration of 25%, 50% and 75% a clear zone (inhibition zone) was formed, whereas at concentrations of 10% and 15% no clear zone (inhibition zone) was formed. From the results of this study it can be concluded that avocado leaf extract can inhibit the growth of Escherichia coli at concentrations of 25%, 50% and 75%.